PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP AGRESIVITAS PAJAK - Pradnyadari, I Dewa Ayu Intan; Rohman, Abdul (Diponegoro Journal of Accounting, 2015)
The purpose of this study is to examine the influence of corporate social responsibility (CSR) with corporate tax aggressiveness. Dependent variable in this study is the tax aggressiveness that measured using proxy of effective tax rates (ETR). Independent variables are corporate social responsibility (CSR). This study used five control variables, include profitability, size, leverage, capital intensity, and inventory intensity.            This study is replication of Lanis and Richardson’s research in 2012 and uses secondary data from annual report of manufacturing companies which listed on Bursa Efek Indonesia in 2011-2013. This study used purposive sampling method and used uses multiple linear regression as the analysis instrument. Before being conducted the regression test, it is examined by using the classical assumption tests.            The result of this study showed that CSR disclosure influence significant negative on corporate tax aggressiveness. Companies with tax aggressiveness would disclose CSR greater than the firm that doesn’t tax aggressiveness. It is because the more efficient a company then the company will pay less tax so that the effective tax rate is also smaller.